Perencanaan Pengambilan Sampel Lampu TL Dop 10 W pada Post Quality Inspection dengan Metode Military Standard 105D di PT. General Electric Lighting Indonesia - Lobes Herdiman; Retno Wulan Damayanti; Sukarno - (Performa: Media Ilmiah Teknik Industri, 2007)
Military standard 105D is a sampling method developed by United States Ministry of Defense. The background of this method development was to accommodate fulfillment of producer and consumer expectation on the product quality inspection with acceptance or rejection lot mechanism. There was three level of inspection based on MLT STD 105D, normal, tightened and reduced. The choice on inspection level, based on tendency of increasing or decreasing defect amount that founded. PT. GE Lighting used a single sampling inspection method with constant sampling amount of 80 pcs for every lot with 500 pcs. This research was to decide the alternative sampling method using MIL STD 105D. Based on the amount of proposal sampling, thus the decreasing percentage on the sample amount from the recent sample of 80 pcs is 37,5% for normal inspection, 40% for reduced inspection and 40% for tightened inspection.The amount sample on each category for the three level inspection on single sampling & double sampling proposal have probability below the producer risk (5%) and consumer risk (10%), so the sampling proposal can accommodate both producer & consumer risk.